Analisis Manajemen Risiko di Lembaga Keuangan Syariah: Kajian Terhadap Praktik dan Tantangan di Bank Syariah - Dhiyanti, Ziyan; Rachmawati, Eva (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2025)
This research addresses the analysis of risk management in Islamic financial institutions, with a particular focus on the practices and challenges faced by Islamic Banks. This research aims to identify and evaluate risk management strategies implemented in the context of Islamic finance, as well as describe the challenges faced by Islamic Banks in implementing effective risk management practices. The research method involves data collection through analysis of relevant documents. The results of this study provide an in-depth insight into the risk management framework implemented by Islamic Banks, identify significant risk factors, and evaluate the institution's response to specific challenges. The practical implications of the findings can assist Islamic financial institutions in improving their risk management effectiveness and facing emerging challenges in a dynamic financial environment.